Design, synthesis, and evaluation of N-(4-(4-phenyl piperazin-1-yl)butyl)-4-(thiophen-3-yl)benzamides as selective dopamine D3 receptor ligands. Issue 18 (15th September 2019) - Chen, Peng-Jen; Taylor, Michelle; Griffin, Suzy A.; Amani, Armaghan; Hayatshahi, Hamed; Korzekwa, Kenneth; Ye, Min; Mach, Robert H.; Liu, Jin; Luedtke, Robert R.; Gordon, John C.; Blass, Benjamin E.
Graphical abstract: Abstract: As part of our on-going effort to explore the role of dopamine receptors in drug addiction and identify potential novel therapies for this condition, we have a identified a series of N-(4-(4-phenyl piperazin-1-yl)butyl)-4-(thiophen-3-yl)benzamide D3 ligands. Members of this class are highly selective for D3 versus D2, and we have identified two compounds (13g and 13r ) whose rat in vivo IV pharmacokinetic properties that indicate that they are suitable for assessment in in vivo efficacy models of substance use disorders.